2013
DOI: 10.1093/eurheartj/eht133
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of myocardial circumferential strain for incident heart failure and cardiovascular events in asymptomatic individuals: the Multi-Ethnic Study of Atherosclerosis

Abstract: http://www.clinicaltrials.gov. Unique identifier: NCT00005487.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
102
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 130 publications
(113 citation statements)
references
References 26 publications
10
102
0
1
Order By: Relevance
“…Previous studies of LV mechanical function and clinically important outcomes in the community have predominantly focused on a single primary measure of LV strain 7, 10, 11. Our study extends previous work by investigating LV strains in different planes and concurrently examining their association with distinct CVD outcomes and mortality.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…Previous studies of LV mechanical function and clinically important outcomes in the community have predominantly focused on a single primary measure of LV strain 7, 10, 11. Our study extends previous work by investigating LV strains in different planes and concurrently examining their association with distinct CVD outcomes and mortality.…”
Section: Discussionmentioning
confidence: 58%
“…Numerous studies have now demonstrated that speckle tracking analyses of LV strain (ie, myocardial tissue deformation) applied to routine echocardiography offer significant incremental prognostic information over EF in patients with known cardiovascular disease (CVD) 4, 5, 6, 7, 8, 9. However, there are few studies of LV strain and outcomes in community‐dwelling individuals free of overt CVD 10, 11. Furthermore, the degree to which distinct components of LV deformation in various planes provide specific prognostic information regarding risk of individual CVD outcomes (eg, coronary disease vs. HF) remains unclear 12, 13…”
Section: Introductionmentioning
confidence: 99%
“…In this study, the author did not measure GLS. 11 In the Framingham Heart Study (n=2831; mean age, 66 years), 12 LV GLS was borderline associated with incident coronary heart events (hazards ratio per SD increment 1.29; P=0.05), whereas circumferential strain was a significant predictor of incident HF (1.79; P<0.0001). Decrements in longitudinal and circumferential strain were significantly related to all-cause mortality in the Framingham study.…”
Section: Discussionmentioning
confidence: 99%
“…9,10 On the contrary, population-based studies are essential to determine the prognostic significance of subclinical LV systolic dysfunction. To date, 2 community-based studies reported on the incremental predictive value of magnetic resonance imaging 11 or echocardioraphically 12 derived LV circumferential strain for incident HF and coronary heart disease. To our knowledge,…”
Section: See Clinical Perspectivementioning
confidence: 99%
See 1 more Smart Citation